2020
DOI: 10.1111/jce.14359
|View full text |Cite
|
Sign up to set email alerts
|

Additional benefits of nonconventional modalities of cardiac resynchronization therapy using His bundle pacing

Abstract: Introduction Dyssynchrony persists in many patients despite cardiac resynchronization therapy (CRT). Aim of this proof‐of‐concept study was to achieve better CRT, with a QRS approximating the normal width and axis, by using His bundle pacing (HBP) and nonconventional pacing configurations. Methods and Results In 20 patients with CRT indications, we performed an acute intrapatient comparison between conventional biventricular (CONV) and three nonconventional pacing modalities: HBP alone, His bundle, and coronar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…In our cohort, successful permanent LBBP was achieved in 88% patients with low and stable capture threshold. The capture threshold was much lower and remained stable during follow‐up compared to that under HBP in previous studies 21 …”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…In our cohort, successful permanent LBBP was achieved in 88% patients with low and stable capture threshold. The capture threshold was much lower and remained stable during follow‐up compared to that under HBP in previous studies 21 …”
Section: Discussionmentioning
confidence: 65%
“…The capture threshold was much lower and remained stable during follow-up compared to that under HBP in previous studies. 21 The LBB fans out directly from the branching point of His bundle to form a network structure beneath the endocardium of the left side of the interventricular septum, which promises pacing the LBB feasibly and rapidly through an interventricular septal method with significant QRS duration shortening. 22 In the present study, better electrical resynchronization was achieved by LBBP-CRT than BiV-CRT.…”
Section: Discussionmentioning
confidence: 99%
“…in an acute study, observed improved pressure‐volume loops with HBP+LV than with biventricular pacing. Coluccia et al, 5 in an acute cross‐over study, showed a better mechanical resynchronization at echocardiographic radial strain analysis with HBP than with conventional CRT.…”
Section: Discussionmentioning
confidence: 97%
“…The implantation procedures were carried out in an electrophysiology laboratory equipped with high resolution fluoroscopy with multiple imaging storing possibilities, as described previously 5 . Patients were connected to an electrophysiology device in such a way as to allow simultaneous 12 lead electrocardiogram (ECG) and intracardiac recordings at different sweep speeds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation